2021
DOI: 10.3389/fimmu.2021.692286
|View full text |Cite
|
Sign up to set email alerts
|

Butorphanol Promotes Macrophage Phenotypic Transition to Inhibit Inflammatory Lung Injury via κ Receptors

Abstract: Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is characterized by diffuse inflammation of the lung parenchyma and refractory hypoxemia. Butorphanol is commonly used clinically for perioperative pain relief, but whether butorphanol can regulate LPS-induced alveolar macrophage polarization is unclear. In this study, we observed that butorphanol markedly attenuated sepsis-induced lung tissue injury and mortality in mice. Moreover, butorphanol also decreased the expression of M1 phenotype mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…The authors induced lung tissue injury in mice via sepsis resulting from intraperitoneal lipopolysaccharide injection, then administered butorphanol to one group of mice whilst the other group remained untreated. They found that mice administered butorphanol had lower numbers of pro-inflammatory and higher numbers of anti-inflammatory macrophages compared to untreated mice ( 128 ). A reduction in pro-inflammatory macrophages result in a reduction in IL-1β, IL-6, and IL-12, whilst an increase in anti-inflammatory macrophages causes an increase in cytokines including IL-10 ( 129 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors induced lung tissue injury in mice via sepsis resulting from intraperitoneal lipopolysaccharide injection, then administered butorphanol to one group of mice whilst the other group remained untreated. They found that mice administered butorphanol had lower numbers of pro-inflammatory and higher numbers of anti-inflammatory macrophages compared to untreated mice ( 128 ). A reduction in pro-inflammatory macrophages result in a reduction in IL-1β, IL-6, and IL-12, whilst an increase in anti-inflammatory macrophages causes an increase in cytokines including IL-10 ( 129 ).…”
Section: Methodsmentioning
confidence: 99%
“…Butorphanol is another commonly used opioid in laboratory animal medicine and is known to have dose-dependent antiinflammatory and immunosuppressive effects (127). One mechanism of the anti-inflammatory action of butorphanol was demonstrated in a study by Luan et al (128). The authors induced lung tissue injury in mice via sepsis resulting from intraperitoneal lipopolysaccharide injection, then administered butorphanol to one group of mice whilst the other group remained untreated.…”
Section: Opioidsmentioning
confidence: 99%
“…For sepsis-induced ALI/ARDS, new drug therapy studies related to this pathway have shown some success. For example, butorphanol significantly reduced sepsis-induced lung tissue injury and mortality by promoting M2 macrophage polarization and inhibiting M1 macrophage polarization through the NF- κ B pathway in a mouse model of sepsis-induced ALI [ 18 ]. M1 macrophages produce proinflammatory factors, such as reactive oxygen species and reactive nitrogen intermediates, as well as the cytokines tumor necrosis factor-alpha (TNF- α ) and IL-6 [ 19 , 20 ].…”
Section: Signaling Pathways Related To Ali/ardsmentioning
confidence: 99%
“…TRIF could activate the transcription factor interferon-responsive factor 3 (IRF3) and then promotes IFNα and IFNβ secretion. Therefore, interferons bind to the interferon receptor (IFNAR) to activate the transcription factor STAT1 to skew macrophages to M1-like or M1 polarization ( 35 ) M1 macrophages are pro-inflammatory to destruct tissue and secrete cytokines, for example, IL-1β, IL-6, TNF-α, and IL-12 ( 36 ). Pro-inflammatory cytokines sustain to recruit immune cells, causing many macrophages to migrate to lesion sites.…”
Section: Different Phenotypes Different Outcomesmentioning
confidence: 99%